Pengaruh Media Sosial Instagram terhadap Minat Berkunjung Wisatawan ke Museum Prabu Geusan Ulun Sumedang - Alia Nurfitri; Dally Nur Arif; Dr.Irena Novarlia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of Instagram social media on tourist interest in visiting the Prabu Geusan Ulun Sumedang Museum. The sample in this study amounted to 100 respondents who were tourists at the Prabu Geusan Ulun Sumedang Museum. The research method used is a descriptive quantitative method with a correlational design that analyses the effect of Instagram social media (X) on tourist interest (Y). The data analysis technique used is simple linear regression to measure the influence and strength of the variable relationship in the study. Hypothesis testing was carried out using the simultaneous f test to determine whether or not there was an influence. The results of this study state that Instagram social media has an influence of 63.2% on tourist interest, with a muscular relationship strength of 0.795. Researchers hope that Prabu Geusan Ulun Sumedang Museum can further develop its Instagram social media to attract tourists, and further research can be conducted with the same theme to develop Prabu Geusan Ulun Sumedang Museum.